CHARACTERISTIC COMPARISION OF CLARK OXYGEN SENSORS MADE FROM DIFFERENT ELECTRODE MATERIALS - Hà, Vũ Thị Thu; Nữ, Đặng Thị Tố (Vietnam Journal of Science and Technology, 2012)
SUMMARY Clark oxygen sensors made from different materials for cathodic electrode have been fabricated successfully. Their behaviors in terms of response time, reproducibility, stability were investigated. The obtained results indicated that studied Clark oxygen sensors using gold single microelectrode, array gold microelectrode, platinum and conventional gold, provide response time: 6s, 10s, 18s and 23s with their residual currents: negligible, 31nA, 63nA and 62nA respectively. There is a good agreement between DO values measured by studied sensors and Winkler titration. The investigation also showed that among studied sensors, the sensor made of gold microelectrode behaves as the best sensor for further application.